Exploring the adoption of less restricted criteria for respiratory syncytial virus prophylaxis in late preterm infants: insights from a retrospective analysis - Mondì, Vito; Paolillo, Piermichele; Bedetta, Manuela; Lucangeli, Natalia; Picone, Simonetta (Frontiers in Pediatrics, 2023)
Background: Preterm infants born between 33 and 35 weeks of gestational age (wGA) have been regarded a “major underserved population” and ineligible to receive pavilizumab (PLV), the only drug authorized to date for RSV prophylaxis, by current international guidelines. In Italy, such vulnerable population is currently eligible for prophylaxis and, in our region, specific risk factors are taken into consideration (SINLazio score) to target prophylaxis to those at highest risk. Whether the adoption of less or more restrictive eligibility criteria for PLV prophylaxis would translate in differences in bronchiolitis and hospitalization incidence is not known. Materials and methods: A retrospective analysis was conducted in 296 moderate-to-late preterm infants (born between 33 and 35+6 weeks) who were being considered for prophylaxis in two epidemic seasons: 2018-2019 and 2019-2020. The study participants have been categorized according to both the SINLazio score and the Blanken risk scoring tool (BRST) which was found to reliably predict RSV-associated hospitalization in preterm infants based on three risk factor variables. Results: Based on SINLazio score, about 40% of infants (123/296) would meet the criteria to be eligible to PLV prophylaxis. In contrast, none of the analyzed infants would be considered eligible for RSV prophylaxis based on the BRST. A total of 45 (15.2%) bronchiolitis diagnoses were recorded on average at 5 months of age in the overall population. Almost seven out of ten (84/123) patients exhibiting ≥ 3 risk factors to be eligible for RSV prophylaxis according to SINLazio criteria would not be receiving PLV if categorized based on BRST. Bronchiolitis occurrence in patients with SINLazio score ≥3 was about 2.2 times more likely than that in patients with a SINLazio score < 3. PLV prophylaxis has been associated with a 91% lower risk of requiring a nasal cannula. Conclusion: Our work further supports the need of targeting late preterm infants for RSV prophylaxis and calls for an appraisal of the current eligibility criteria for PLV treatment. Therefore, adopting less restrictive criteria may ensure a comprehensive prophylaxis of the eligible subjects thus sparing them from avoidable short and long-term consequences of the RSV infection.